The Effect of Cross-linking Agents on Oil Palm Empty Fruit Bunch Fiber-Grafted Polyvinyl Alcohol (PVA) Hydrogel - Devan, Vaaghisen (Universiti Teknologi PETRONAS, 2016)
The aim of this project was to study the effect of cross-linking agents on Oil Palm Empty Fruit Bunch (OPEFB) fiber-grafted polyvinyl alcohol (PVA) hydrogel especially in the aspects of Water Absorbency Capacity (WAC), thermal and structural properties of the hydrogel. The crosslinking agent that was used in this project was NN’ Methylene Diacrylamide, Diethylene Glycol, Ethylene Glycol and Sodium Borate. These hydrogels were compared and studied under several tests such as Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) are conducted to study its thermal properties, Scanning Electron Microscope (SEM) and Fourier Transform Infrared (FTIR) Spectroscopy is conducted to study its structural properties and finally the Water Absorbency Capacity test. Based on the results, a hydrogel with more porous structure will give a good WAC and a hydrogel with the least porous structure will show good thermal properties. Hence, N-N’ Methylene Diacrylamide hydrogel was taken as the best hydrogel because it has a good WAC at 123% and good thermal properties whereby the temperature of glass transition (Tg) for TGA is 2500C.